Safety and efficacy of EUS-guided pancreatic duct drainage in symptomatic main pancreatic duct obstruction: Is there still a place for surgery? - Falque, Arthur; Gasmi, Mohamed; Barthet, Marc; Gonzalez, Jean-Michel (Endoscopy International Open, 2021)
Background and study aims In patients with symptomatic dilation of the main pancreatic duct (MPD) for whom endoscopic retrograde cholangiopancreatography (ERCP) is impossible, surgery has long been the only available treatment. EUS-PD is described as a minimally invasive alternative for ductal decompression surgery. We describe the results of our experience with it.Patients and methods This was a retrospective single-center study over 9 years. Twenty-seven patients, median age 61.8 years (range 36 to 85) who underwent EUS-PD for symptomatic MPD dilatation were included. The main objective was to evaluate the technical success (placement of a plastic stent between the stomach and the MPD). Secondary objectives were to document clinical success based on pain and quality of life (visual analogic scales and treatments) and complication rates, and to define a standardized management algorithm.Results The technical success rate was 92.5 %. The rate of minor adverse events was 21 % (4 cases of non-specific postoperative pain and two cases of delayed benign edematous pancreatitis). The clinical success rate was 88 %, and half of patients in whom the procedure was successful had "complete regression" of pain and half "partial regression." Median follow-up was 34.2 months (range 4 to 108). During follow-up, 74 % of patients reported improvement in quality of life and no patients required secondary surgery.Conclusion Provided it is performed in an expert center, EUS-PD is a minimally invasive, effective, and safe alternative to pancreatic surgical drainage in patients with symptomatic MPD dilatation with failure or in whom ERCP is impossible.